Influence of Partially Standing Waves on Offloading Operations for Shuttle Tanker - Patel, M.S. (Springer, 2020)
The side-by-side configuration of a shuttle tanker undergoes more complex hydrodynamic behavior. This is more critical in extreme weather conditions. The gap between the FPSO and shuttle tanker adds to complexity of hydrodynamic behavior. Past studies have been performed to understand the gap resonance and other behavior of water column between the FPSO and shuttle tanker. This paper aims to study the effect of partially standing waves on the offloading operation, which occurs between the gap of FPSO and shuttle tanker pertaining to different encountering time period of waves for shuttle tanker. The velocity potential and wave kinematics of partially standing waves are derived and subsequently the different percentage of reflected wave height on the wave kinematics are studied. The objective of studying the influence of partially standing waves offloading operation is achieved by studying two types of waves as moderate and extreme waves. The higher wave height affects the kinematics of waves between the vessels. Also, the higher percentage of reflected wave height contributes to greater kinematics of waves. The conclusions of study and scope of future work is presented at the end. Â© 2020, Springer Nature Singapore Pte Ltd.